How do soccer players sprint from a tactical context? Observations of an English Premier League soccer team - Caldbeck, P.; Dos'Santos, T. (Journal of Sports Sciences, 2022)
The aim of this study was to quantify and tactically contextualise (i.e., phase of play and tactical outcome [TO]) sprints (=7.0 m/s) of an English Premier League (EPL) soccer team during match-play. Videos of 901 sprints (10 matches) were evaluated using the Football Sprint Tactical-Context Classification System. Sprints occurred within a variety of phases of play (attacking/defensive organisation and transitions) and TOs, both out- and in-possession, with position-specific differences. Most sprints were completed out-possession (58%), with "closing down" the most observed TO (28%). In-possession, "run the channel" (25%) was the most observed TO. Centre backs predominantly performed "ball down the side" sprints (31%), whereas central midfielders mostly performed "covering" sprints (31%). Central forwards and wide midfielders mostly performed "closing down" (23% and 21%) and "run the channel" (23% and 16%) sprints when out- and in-possession, respectively. Full backs most frequently performed "recovery" and "overlap" runs (14% each). This study provides insights into the specific physical-tactical characteristics of sprints performed from an EPL soccer team. This information can be used to assist in the development of position-specific physical preparation programmes, and more ecologically valid and contextualised gamespeed and agility sprint drill construction to better reflect the demands of soccer.